Pengaruh Tingkat Birokrasi, Sentralisasi Pengambilan Keputusan, Kompleksitas Prosedur Operasional Standar, dan Jumlah Pelaporan Administratif terhadap Kelincahan Organisasi : (Studi pada RS “I”) - Daniel Setiawan Nathan; Rian Andriani; Rinawati Rinawati (Jurnal Ilmiah Dan Karya Mahasiswa, 2026)
Introduction: Organizational agility is an essential strategic capability for healthcare institutions navigating regulatory dynamics, technological transformation, and evolving service demands. Bureaucracy level, decision-making centralization, standard operating procedure (SOP) complexity, and administrative reporting quantity are structural factors that significantly determine hospital organizational agility. Methods: An explanatory quantitative survey study was conducted on all 75 employees of “I” Hospital, using saturated sampling. A Likert scale 1–5 questionnaire met validity (r-calculated > 0.227) and reliability standards (Cronbach's α ≥ 0.972). Multiple linear regression was performed via SPSS. Results: All independent variables showed positive and significant effects on organizational agility both partially and simultaneously: bureaucracy level (β=0.594; p=0.000), decision-making centralization (β=0.113; p=0.025), SOP complexity (β=0.308; p=0.019), and administrative reporting quantity (β=0.031; p=0.032). Simultaneous testing yielded F=1056.152 (p=0.000) with R²=0.984. Bureaucracy level was the most dominant predictor (standardized β=0.559). Discussion: Adaptively structured bureaucracy, effective centralization, systematic SOPs, and well-managed administrative reporting synergistically enhance organizational agility through dynamic capabilities mechanisms. Conclusion: All four structural variables jointly contribute significantly to enhanced organizational agility at “I” Hospital, West Bandung Regency.